Implementasi Sistem Informasi Pemesanan pada Percetakan @M Grafika Berbasis Website Menggunakan Metode Waterfall - Azhar Ali Akbar; Muhammad Farrel Gunawan; Raihan Ramadhan; Ines Heidiani Ikasari (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of information technology has significantly influenced various business sectors, including the printing industry. This study aims to implement a web-based ordering information system at @M Grafika to improve efficiency and accuracy in business processes. The system was developed using the Waterfall model, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The application was built using PHP as the programming language, MySQL as the database, and Bootstrap as the front-end framework to ensure a responsive interface. The results show that the system enables customers to place orders online, upload design files, and confirm payments easily. Meanwhile, administrators can manage product data, portfolios, and customer orders in an integrated manner. The implementation of this web-based ordering system has proven to enhance operational effectiveness and service quality at @M Grafika